Proceedings of the 1992 Symposium on Autonomous Underwater Vehicle Technology
DOI: 10.1109/auv.1992.225178
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive testing of controllers for autonomous vehicles

Abstract: Autonomous vehicles are likely to require sophisticated software controllers to maintain vehicle performance in the presence of vehicle faults. The test and evaluation of complex software controllers is expected to be a challenging task. The goal of this effort is to apply machine learning techniques from the field of artificial intelligence to the general problem of evaluating an intelligent controller for an autonomous vehicle. The approach involves subjecting a controller to an adaptively chosen set of faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…fuzzy logic), Li, Nutter (1990) dirbtinių neuroninių tinklų (angl. neural nets), Schultz et al (1992) -genetinio programavimo (angl. genetic algorithm) metodais pagrįstus algoritmus.…”
Section: įVadasunclassified
“…fuzzy logic), Li, Nutter (1990) dirbtinių neuroninių tinklų (angl. neural nets), Schultz et al (1992) -genetinio programavimo (angl. genetic algorithm) metodais pagrįstus algoritmus.…”
Section: įVadasunclassified
“…While, the GA approach presented in this paper is unlike other published approaches to the application of GA to support software testing or software quality assessment, the "failure-pursuit sampling" work of [Dickinson et al 2001] and the "adaptive testing" work of [Schultz et al 1992] are particularly noteworthy with respect to their motivation for the work of this paper.…”
Section: Figure 2 Basic Steps Of a Typical Genetic Algorithmmentioning
confidence: 99%
“…[ Schultz et al 1992] demonstrated the use of adaptive testing to test intelligent controllers for autonomous vehicles by creating individuals in the population that represented fault scenarios to be supplied to simulators of the autonomous vehicles. A benefit of such testing was to provide more information to the developers.…”
Section: Figure 2 Basic Steps Of a Typical Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, knowledge about the program structure is necessary for Wegener's approach to work, whereas our method does not depend on the program structure at all. [7] also uses evolutionary methods to evolve new tests for a controller, but out of a set of known faults of this controller. Obviously, this is mainly a recombination effort, not the construction of a new threat, as in our approach.…”
Section: Evolutionary On-line Learning For Threat Testingmentioning
confidence: 99%